2022
DOI: 10.3390/vetsci9110607
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies on the Intrahepatic Anatomy of the Venous Vasculature in Cats

Abstract: Hepatic surgeries are often performed in cats to obtain a disease diagnosis, for the removal of masses, or for the treatment of shunts. Whereas the vascular anatomy of the liver has been studied in dogs, such evidence is lacking in cats. The current study used corrosion casts of portal and hepatic veins and computed tomography (CT) analysis of the casts to identify and describe the intrahepatic anatomy in healthy cat livers (n = 7). The results showed that feline livers had a consistent intrahepatic portal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Results from the current research show that the use of anatomical dissections injected with colored latex helps in the identification of the major blood vessels as well as their main branches and this enhances the anatomical accuracy of the study. Our study concurs with other authors who have used anatomical preparations with vascular repletion to facilitate the examination of the vasculature of the abdominal and pelvic cavities [ 25 , 27 , 28 ]. In our work, CTA images were acquired by means of a 16-slices spiral CT unit, which contributed a suitable view of the abdominal and pelvic vascular system.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results from the current research show that the use of anatomical dissections injected with colored latex helps in the identification of the major blood vessels as well as their main branches and this enhances the anatomical accuracy of the study. Our study concurs with other authors who have used anatomical preparations with vascular repletion to facilitate the examination of the vasculature of the abdominal and pelvic cavities [ 25 , 27 , 28 ]. In our work, CTA images were acquired by means of a 16-slices spiral CT unit, which contributed a suitable view of the abdominal and pelvic vascular system.…”
Section: Discussionsupporting
confidence: 92%
“…In our work, CTA images were acquired by means of a 16-slices spiral CT unit, which contributed a suitable view of the abdominal and pelvic vascular system. The reviewed literature contained a few studies on feline abdominal and pelvic anatomy using CTA [ 24 , 25 , 26 , 27 , 28 , 29 ]. Other researchers have applied CTA for the assessment of the characteristics of the renal vessels in healthy cats for the selection of appropriate feline renal transplant donors [ 30 , 31 , 32 ], and there is also one recent report that combine CTA VR reconstructions, anatomical dissections and 3D printings for the study of the vascularization and bile circulation of the feline liver [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood supply in the feline liver is provided by the hepatic artery, which is a branch of the celiac artery, and the portal vein, which provides 80% of the blood supply to the liver [ 20 , 68 ]. Recently, Metzger et al described the vascular anatomy of the liver in seven healthy cats [ 119 ]. Based on their results, it was reported that the portal vein, upon entering the liver hilus, is divided into a right and left branch, giving branches to the liver lobes, in contrast to previous reports for three branches [ 68 ] ( Figure 26 ).…”
Section: Digestive Glandsmentioning
confidence: 99%